Formação em exercício de professores dos anos iniciais: habilidades visuais no ensino e aprendizagem de geometria - Monteiro, Francine Lanes (2014)
This dissertation presents a research realized an a professional master's degree in teaching of mathematics. It aimed to investigate what contributions can offer an educational workshop to develop visual abilities in geometry by teachers on the early years of elementary school. In order to answer the research problem it was decided to organize it in the following topics: visual abilities can be developed with these teachers about workshops? Construction and use of didactic materials help on the acquisition of visual abilities? Helds activities with puzzles make possible the acquisition of visual activities? The research was characterized as qualitative who subjects were eight teachers. They are teachers in class on a Public School of Basic Education of the City of Júlio de Castillos on the state of Rio Grande do Sul, in Brazil. The instruments to collect data were questionnaires and written records by them and the researcher. The research was conducted in four stages, namely: initial questionnaire, syllabus analysis of the early years, teaching workshops and final questionnaire. profile of the group of teachers who work in the early years of this school, his views on mathematics education. The group researched profile can be regarded as experienced and qualified, therefore, all of them having higher education in Pedagogy and only three of them, do not have graduate. It was noticed was how fragile the mathematical training of these teachers, fear and superficiality to talk about mathematics and geometry. The syllabus of the analysis showed that there are gaps in the second geometry content for four years, since they do not appear in the third. In turn, such content, when they appear, are on the list, or are planned to be developed by the end of the school year. From these two stages of the research, it was planned two workshops with specific activities involving visual skills, which, involved three types of skills: perception of figures in fields, visual discrimination and visual memory. In the workshops there was a need for activities are offered that include the development of visual skills, since some teachers had difficulties in memorizing and compare figures. It was found also that visual skills contribute significantly to the formation of geometric thinking and the importance of manipulatives in developing these skills. It was evidenced by the final questionnaire the group satisfaction studied in relation to the development of the workshops. We conclude that continuing education is a moment of great importance for the expansion and consolidation of knowledge. Justified the use of the term in-service training of teachers in the title of this work because the research was conducted with teachers who work effectively in the early years of elementary school. However, the focus of the dissertation was not the teacher training itself, but the development of visual skills in the teaching of geometry.